Decreasing number of distance shooting in handball - trend of nowadays male handball competition - Smolarczyk Marcin (Sciendo, 2023)
The aim of this study was to analyze and compare performance data structure in two consecutive EHF Men's EURO competition in 2020 and 2022 in order to highline significance of differences in two-year cycle of European Championships.